Women and gender equity in development theory and practice : institutions, resources and mobilization - Jaquette, Jane S., ed.; Summerfield, Gale, ed. (Durham, N.C : Duke University Press, 2006)
Extrait de la couverture : "Highlighting key institutional issues, contributors analyze the two approaches that dominate the field: women in development (WID) and gender and development (GAD). They assess the results of gender mainstreaming, the difficulties that development agencies have translating gender rhetoric into equity in practice, and the conflicts between gender and the reassertion of indigenous cultural identities. Focusing on resource allocation, contributors explore the gendered effects of land privatization, the need to challenge cultural traditions that impede women's ability to assert their legal rights, and women's access to bureaucratic levers of power. Several essays consider women's mobilizations, including a project to provide Internet access and communications strategies to African NGOs run by women. In the final essay, Irene Tinker, one of the field's founders, reflects on the interactions between policy innovation and women's organizing over the three decades since women became a focus of development work. Together the contributors bridge theory and practice to point toward productive new strategies for women and gender in development."
Preface and Acknowledgments viiIntroduction / Jane S. Jaquette and Gale Summerfield 1I. Institutional Opportunities and Barriers 15Women, Gender, and Development / Jane S. Jaquette and Kathleen Staudt 17Mainstreaming Gender in International Organizations / Elisabeth Prugl and Audrey Lustgarten 53From "Home Economics" to "Microfianace:; Gender Rhetoric and the Bureaucratic Resistance / David Hirschmann 71Contributions of a Gender Perspective to the Analysis of Poverty / Sylvia Chant 87What is Justice? Indigenous Women in Andean Development Projects / Maruja Barrig 107II. Livelihood and Control of Resouces 135Gender Equity and Rural Land Reform In China / Gale Summerfield 137Unequal Rights: Women and Property / Diana Lee-Smith and Catalina Hinchey Trujillo 159On Loan from Home: Women's Participation in Formulating Human Settlements Policies / Faranak Miraftab 173In Theory and in Practice: Women Creating Better Accounts of the World / Louise Fortmann 191Women's Work: The Kitchen Kills More than the Sword / Kirk R. Smith 202III. Women's Mobilization and Power 217Women's Movements in the Globalizing World: The Case of Thailand / Amara Pongsapich 219T-Shirts to Web Links: Women Connect! Communications Capacity-Building with Women's NGOs / Doe Mayer, Barbara Pillsbury, and Muadi Mukenge 240Empowerment Just Happened: The Unexpected Expansion of Women's Organizations / Irene Tinker 268Acronyms 303Bibliography 306Contributors 352Index 357
Includes bibliographical references
Keywords: Women in development; Women -- Developing countries -- Social conditions; Women's rights